MICROALGAE AS MULTIFUNCTIONAL FEED ADDITIVES IN POULTRY: ROLES IN NUTRITION, HEALTH AND PRODUCT QUALITY - R. Richard Churchil; S. Meignanalakshmi (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Microalgae have gained increasing attention as multifunctional feed ingredients in poultry nutrition due to their rich content of bioactive compounds, including pigments, polyunsaturated fatty acids, vitamins, minerals, polysaccharides, and secondary metabolites. This review summarizes experimental evidence on the functional properties of major microalgal species such as Spirulina (Arthrospira platensis), Chlorella spp., Haematococcuspluvialis, Nannochloropsis, Schizochytrium, and other marine microalgae in poultry diets. Emphasis is placed on their antioxidant, antimicrobial, anti-inflammatory, immunomodulatory, and gut healthpromoting effects. Microalgal supplementation enhances endogenous antioxidant defence systems, modulates cytokine responses, suppresses enteric pathogens, and improves intestinal morphology and microbiota composition. These functional effects translate into improved stress tolerance, immune competence, nutrient utilization, and overall bird health. In addition, microalgae positively influence poultry product quality by enhancing yolk pigmentation, enriching eggs and meat with omega-3 fatty acids, and improving oxidative stability and sensory attributes. Variability in responses across studies is largely associated with differences in algal species, inclusion level, processing form, duration of feeding, and physiological status of birds. Overall, microalgae represent promising natural feed additives for sustainable poultry production, although further research  is  needed  to  optimize  their  practical  application  at  commercial  scale.